Pengaruh Etos Kerja dan Disiplin Kerja terhadap Kinerja Pegawai pada Dinas Perhubungan Kota Bima - Jumriyani Istiqomah; Firmansyah Kusumayadi; Rahmatia Rahmatia (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to determine whether or not there is an influence of work ethic and work discipline on the performance of employees at the Bima City transportation service. The research method used is associative research. The sample for this research was 34 ASN employees, with the sampling technique used, namely purposive sampling, analytical tools. The validity test, reliability test, classical assumption test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple linear test, multiple correlation coefficient, determination test, f test and t test are used. The aim is to find out whether work ethic has a significant effect. partially on the performance of employees at the Bima City Transportation Service, Does work discipline have a partially significant effect on employee performance at the Bima City Transportation Service, Does work ethic and work discipline simultaneously have a significant effect on the performance of employees at the Bima City Transportation Service.